2015
DOI: 10.1002/2015ja021235
|View full text |Cite
|
Sign up to set email alerts
|

Wave structure and polarization electric field development in the bottomside F layer leading to postsunset equatorial spread F

Abstract: In this paper we present the results of a study on the characteristics of large‐scale wave structure in the equatorial ionospheric F region that serve as precursor to postsunset development of the spread F/plasma bubble irregularities. The study is based on analysis of Digisonde data from three equatorial sites in Brazil (Fortaleza, Sao Luis, and Cachimbo) for a period of about 2 months at a medium solar activity phase. Small‐amplitude oscillations in the F layer heights, extracted at a number of plasma freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…Abdu et al () analyzed the digisonde data from October to November 2001, at three sites in the equatorial region of Brazil, during the period of plasma bubbles. They found that the F ‐layer oscillations between 12:00 LT and dusk period may be the precursor of plasma bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Abdu et al () analyzed the digisonde data from October to November 2001, at three sites in the equatorial region of Brazil, during the period of plasma bubbles. They found that the F ‐layer oscillations between 12:00 LT and dusk period may be the precursor of plasma bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Equatorial plasma bubbles (EPBs) are large‐scale plasma depletions that originate over the dip equator in the nighttime F region ionosphere due to the generalized Rayleigh‐Taylor instability process. The instability is triggered by perturbations in the bottomside F region [ Kelley et al , ; McClure et al , ; Sekar et al , ; Abdu et al , , ; Narayanan et al , ] when the background ionosphere in the post sunset hours is favorable for growth of the instability [ Abdu et al , ; Jayachandran et al , ; Fejer et al , ]. They often grow to the topside ionospheric altitudes within few tens of minutes [ Sultan , ; Sidorova and Filippov , ; Patra et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The F layer vertical drifts averaged for the two groups of days, the red and blue curves corresponding to the first group and second group, respectively, (bottom) the smaller amplitude (random) oscillations. Based on the well-known role of the E layer tidal winds in shaping the longitudinal/local time gradient in the E layer conductivity at sunset (Abdu et al 2003), the above results suggested possible tidal modes-gravity wave coupling process impacting on the PRE-ESF relationship (for further details, see Abdu et al 2015b). This appears to be an important connecting link in determining the precursor conditions for the plasma bubble/ESF irregularity development.…”
Section: Gravity Wave Effects On Equatorial Spread Fmentioning
confidence: 99%
“…8 wherein we note height oscillations of significant amplitude during the daytime, getting amplified toward evening hours and further increasing in amplitude as a result of the post-sunset spread F/bubble irregularities that they initiated, as indicated by the gray segment of each curve (with some exceptions that is determined by the PRE vertical drift amplitude, not shown here). It was shown by Abdu et al 2015b that these height oscillations were driven by polarization electric field induced by upward propagating gravity waves, which therefore represented the precursor seed required for ESF instability growth. An intriguing aspect of the results in Fig.…”
Section: Gravity Wave Effects On Equatorial Spread Fmentioning
confidence: 99%
See 1 more Smart Citation